Elements of Optimal Monetary Policy Committee Design - Vandenbussche, Jerome (IMF Working Papers; Working Paper ;, 2006)
The move from individual decision making to committee decision making is widely seen as a major evolution in contemporary central banking. This paper reviews the relevant economics and social psychology literatures with a view to providing some insights into the question of optimal monetary policy committee design. While the preference aggregation literature points to the effect of committee structure on the extent of the time inconsistency problem and its associated costs, the belief aggregation literature analyzes how different committee structures affect the efficiency of information pooling, the process of social influence, and collective accuracy. In conclusion, we highlight the main tradeoffs that the analysis has brought to light and point to directions for future research.